2012
DOI: 10.1152/ajpheart.00032.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase inhibition augments central blood pressure and aortic wave reflection in aging humans

Abstract: The augmentation index and central blood pressure increase with normal aging. Recently, cyclooxygenase (COX) inhibitors, commonly used for the treatment of pain, have been associated with transient increases in the risk of cardiovascular events. We examined the effects of the COX inhibitor indomethacin (Indo) on central arterial hemodynamics and wave reflection characteristics in young and old healthy adults. High-fidelity radial arterial pressure waveforms were measured noninvasively by applanation tonometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Because we infused a nonselective inhibitor of cyclooxygenase, it is likely that vasodilating prostaglandins were also inhibited, and this may contribute to the rise in MAP observed at rest in healthy subjects (35). Ketorolac could also raise arterial stiffness and central BP, which has been shown in previous studies (4,5).…”
Section: Discussionmentioning
confidence: 64%
“…Because we infused a nonselective inhibitor of cyclooxygenase, it is likely that vasodilating prostaglandins were also inhibited, and this may contribute to the rise in MAP observed at rest in healthy subjects (35). Ketorolac could also raise arterial stiffness and central BP, which has been shown in previous studies (4,5).…”
Section: Discussionmentioning
confidence: 64%
“…In a previous study, we found that INDO augmented central blood pressure and aortic wave reflection in older individuals (Barnes et al . ). These changes in central haemodynamics, in conjunction with the slightly attenuated response to RH after INDO in older adults in the present study, reinforce the theory that older individuals have a limited ability to compensate for the acute haemodynamic shifts induced by INDO.…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, it appears that COX inhibition has unfavourable effects on both central haemodynamics (Barnes et al . ) and peripheral vascular responses to RH in older adults. Importantly, these results were found in healthy older adults and in response to only a single administration of INDO.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All measurements were performed by a trained medical doctor in duplicate, and the mean of these measurements was used in further analysis. Left ventricular wasted energy (E w ), which is the component of extra-myocardial O 2 requirement due to early systolic wave reflection, was estimated according to equation reported by Barnes et al (2012). AIx 75 was calculated as AIx adjusted for a HR of 75 beats min À1 .…”
Section: Assessment Of Arterial Stiffnessmentioning
confidence: 99%